Kronikarz spóźnionej wojny. Woń człowieka Ernő Szépa - Piotrowiak-Junkiert, Kinga (Slavia Occidentalis, 2015)
The article presents a portrait of one of the most important witnesses of the Holocaust in Hungary, the author of Emberszag and „the legend of Ernő Szép”, who would greet people by saying „I was Ernő Szép”. In his innovative work, the writer draws upon his skills as both reporter and observer. The way he can intricately interweave different episodes confirms his great artistic ability, but most of all it highlights the essential need to accord to the Jewish history all the respect it deserves. Szép achieves this through adopting an anthropocentric perspective – each scene focuses primarily on human emotions and habits, whilst the key context of all the events – the Shoah – is shifted to the background. Without overloading the text with too many dates or legal references, Szép pays careful attention to facts which gives readers a perfect opportunity to recreate the successive stages of the Jewish history in 1944 Budapest.